BIOM-31. ERK1/2 PHOSPHORYLATION PREDICTS SURVIVAL FOLLOWING ANTI-PD-1 IMMUNOTHERAPY IN RECURRENT GLIOBLASTOMA. (12th November 2021) - Arrieta, Víctor; Chen, Andrew X; Kane, J Robert; Kang, Seong Jae; Kassab, Cynthia; Dmello, Crismita; Zhao, Junfei; Burdett, Kirsten; Upadhyayula, Pavan; Chang, Catalina; Shilati, Joseph; Jaishankar, Dinesh; et al.
Abstract: PD-1 checkpoint inhibition has led to remarkable clinical responses in several cancer types. Whereas PD-1 blockade has not shown an overall survival (OS) benefit for glioblastoma (GBM) patients, a subset of them exhibit long-term responses to this immunotherapy. Previously, we reported an enrichment of BRAF/PTPN11 activating mutations in 30% of recurrent GBMs that responded to PD-1 blockade, but the molecular profile of the majority of responders remained elusive. Given that BRAF and PTPN11 promote MAPK/ERK signaling, we investigated whether activation of this pathway is associated with response to PD-1 inhibitors in recurrent GBM, including patients that do not harbor BRAF/PTPN11 mutations. Immunohistochemistry for ERK1/2 phosphorylation (p-ERK), a marker of MAPK/ERK pathway activation, was performed in a discovery cohort including pre-treatment specimens of 29 recurrent GBM patients treated with adjuvant PD-1 blockade, and 33 patients who did not undergo immunotherapy. p-ERK was predictive of response and OS following PD-1 blockade. Yet p-ERK was not associated with OS in patients not treated with immunotherapy. p-ERK was also associated with OS in a validation GBM cohort treated with adjuvant anti-PD-1 therapy. Single-cell RNA-seq and multiplex-immunofluorescence analyses revealed that p-ERK was mainly localized in tumor cells and high p-ERK GBMs contained tumor-infiltrating myeloid cells and microglia with elevated expression of MHC class II and associated genes. Thus, our findings indicate that ERK1/2 activation in recurrent GBM is predictive of response to PD-1 blockade and is associated with a distinct myeloid cell phenotype.